Multicultural and International Research in Four Career Development Journals: An 11‐Year Content Analysis. Issue 4 (7th December 2017) - Garriott, Patton O.; Faris, Eve; Frazier, Julian; Nisle, Stephanie; Galluzzo, Joseph
Abstract : In an increasingly diverse and global society, it is important to evaluate the cultural responsiveness of vocational research. The authors examined trends in the publication of multicultural‐focused articles from 2005 to 2015 in 4 journals: The Career Development Quarterly, the Journal of Career Assessment, the Journal of Career Development, and the Journal of Vocational Behavior . Methodological, thematic, and construct trends were examined across the identity categories of gender, socioeconomic status, sexual orientation, gender identity, ability status, religion/spirituality, age, immigration status, and international research. Results showed increases in social class and international research but continued neglect of sexual orientation, gender identity, and ability status. The themes of career exploration and promoting agency received the most attention; equity in work settings received the least. Findings suggest that more research with underrepresented groups is needed and that counselors may need to rely on resources outside the current literature to ensure best practices with these clients.